Surprise! From CEOs to Navy SEALs: How a Select Group of Professionals Prepare for and Respond to the Unexpected - Baiocchi, Dave (RAND Corporation, 2013)
This report relates what professionals believe creates surprise, how they respond to it, and how the effects of surprise can be mitigated. RAND researchers interviewed representatives from 13 diverse professions and identified some common coping strategies, such as relying on past experience and trying to reduce the level of chaos in the environment.